Implementation of Leadership Strategy to Realize the Transformation Digital towards Smart Military University - Sigit Anggoro; Diding Nurdin; Sururi (Jurnal Pendidikan dan Pengajaran, 2023)
The digitalization process towards a smart university requires adequate leadership support. The research objective is to analyze the implementation of leadership strategy to realize Digital transformation towards a smart military university (SmU). The mix method exploratory sequential design approach was chosen based on the uniqueness of the leadership style which is rich with a variety of approaches due to situational demands and cultural development. Qualitative data collection was carried out by in-depth interviews. Research participants consist of strategic decision makers, and academic staff who are involved in the digital transformation process. The collected data was analyzed using content analysis techniques to identify the main themes in relation to the smart military university. Quantitative analysis based on the results of path analysis to support qualitative findings involving 128 random respondents. The results of this study indicate that the implementation of an effective leadership strategy has an important role in realizing digital transformation towards a Smart Military University. Various situational challenges are key factors in the implementation of various leaderships to optimize their effectiveness. It can be concluded that the military leadership approach is combined with transformational to inspire and motivate change. A complexity leadership approach that focuses on recognizing that digital transformation processes tend to be unpredictable and complex, helping institutions and individuals to adapt, more flexibility, encouraging collaboration, and systemic thinking skills. The practical implication of this research is the importance of developing collaborative and transformational leadership among military leaders to face challenges and opportunities in the digital era.